Social differentiation and increasing social heterogeneity in Leipzig, Germany, in light of daily life perceptions and policy-making - Haase, Annegret; Budnik, Maria; Großmann, Katrin; Haid, Christian; Hedtke, Christoph; Kullmann, Katharina (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
Social differentiation has developed to be one of the crucial characteristics of urban development in Eastern Germany’s large cities, an issue that is increasingly reflected in daily life perceptions and policy-making. This development can be especially observed in those cities that, after a phase of shrinkage in the 1990s, have seen new growth during the last years. The focus is here on social differentiation that we understand as an increase in social inequalities, and on social heterogeneity that is understood as pluralization of cultural and religious identities, lifestyles and living environments. Set against this background, the paper discusses social differentiation and increasing heterogeneity in Leipzig with a focus on daily life perceptions by the residents and local policy development. It analyses how social difference and increasing heterogeneity have become an issue for daily routines and practices as well as for policy formulation and how both perspectives interact. The paper is based on a multi-dimensional understanding of heterogeneity including the socio-economic, demographic, lifestyle and ethnic-migration dimension. Spatially, both the total city and neighbourhood perspective are in focus. The paper concludes, among others, that social heterogeneity in its horizontal dimension is being recognised and accepted and that this is reflected by policy development as well. This does not apply in the same manner for increasing social inequalities. The example of Leipzig shows, furthermore, that there is a need for more differentiation in the local discourse with respect to the explicit recognition of horizontal difference, the need to counteract vertical social inequalities and the fact that out of the interaction/intersection of both dimensions, a bundle of new equivocalities and complexities emerge.